Picture perfect posing : practicing the art of posing for photographers and models - Valenzuela, Roberto (San Francisco, California : New Riders, 2014)
Photographer, author, and educator Roberto Valenzuela has a proven track record for teaching and explaining difficult concepts to photographers of all skill levels. His remarkable ability to break down complicated ideas into understandable, approachable elements that photographers can truly grasp-and then use their newfound knowledge to improve their photography-made his first book, Picture Perfect Practice, a breakout success. In Picture Perfect Posing, Roberto takes on the art of posing. For many photographers, after learning to compose an image and even light it properly, a portrait can still easily be a failure if the pose is not natural, elegant, and serving the needs of both the subject and the photographer. Instead of just showing page after page of poses-like most posing books on the market-Roberto actually breaks down the concept of posing by examining the anatomy, starting with the core foundation: the spinal chord and neck. Building from there, Roberto discusses every component of what makes poses work, as well as fail. How should the model hold her hands? Bend her elbows? Position her fingers? Should the model look toward or away from the camera, and why? It all depends on what the photographer wants for the shot, and Roberto discusses the entire process, from the intent of the photographer through the execution of the pose. For those who have been discouraged by an inability to pose their subjects, or who have simply not known where to start in order to "figure it out," Picture Perfect Posing is the essential resource they need to learn how posing truly works, and how they can learn to direct the exact pose they need for the shot they want.
Includes index.
Keywords: Glamour photography